On the exploitation of portunid crab Podophthalmus vigil (Weber) along the Chennai coast in Tamil Nadu - Subrahmanyan, V Thankaraj (Indian Journal of Fisheries, 2011)
The trend in catch of Podophthalmus vigil at Chennai during 1984-'98 showedslow increase from stray occurrence to a small fishery in 1980's to be followed byan upsurge with the annual catch over lOOt during 1992-'95. After reaching themaximum catch of 217t in 1994-'95, the catch declined drastically to 61 in 1997-'98. The main fishery season was September-January. Males were relativelylarger and heavier. Average sex-ratio was 55.2 : 44.8. Peak spawning activitieswere recorded in October and January.